2000
DOI: 10.2225/vol3-issue1-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic microorganisms: a review on insect control and recent advances on tropical plants

Abstract: In the past two decades, a great deal of information on the role of endophytic microorganisms in nature has been collected. The capability of colonizing internal host tissues has made endophytes valuable for agriculture as a tool to improve crop performance. In this review, we addressed the major topics concerning the control of insects-pests by endophytic microorganisms. Several examples of insect control are described, notably those involving the interactions between fungi and grazing grasses from temperate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
320
0
100

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 557 publications
(444 citation statements)
references
References 100 publications
4
320
0
100
Order By: Relevance
“…Endophytes are microbes that inhabit plant tissues in their life cycle without causing any apparent harm to their host [2] . Their presence implied a symbiotic interaction, in all the plants investigated until now [3] . Metal nanoparticles show promising applications in the fields of medicine, electronics, agriculture, etc.…”
Section: Introductionmentioning
confidence: 87%
“…Endophytes are microbes that inhabit plant tissues in their life cycle without causing any apparent harm to their host [2] . Their presence implied a symbiotic interaction, in all the plants investigated until now [3] . Metal nanoparticles show promising applications in the fields of medicine, electronics, agriculture, etc.…”
Section: Introductionmentioning
confidence: 87%
“…The biotechnological progresses are allowing the identifi cation of endophytic microorganisms promising for insect biological control (Azevedo et al 2000). Azevedo & Araújo (2007) defi ned endophytes as all the microorganisms that inhabit the interior of the host plant, without causing apparent damages or visible external structure.…”
Section: Abstract: Insecta Oryza Sativa Endophytic Microorganismmentioning
confidence: 99%
“…Azevedo & Araújo (2007) defi ned endophytes as all the microorganisms that inhabit the interior of the host plant, without causing apparent damages or visible external structure. The presence of endophytic microorganisms inside the host plant may increase the plant fi tness by protecting it against pest and pathogens, improving plant growth and increasing resistance in stressful environments (Azevedo et al 2000, Scherwinski et al 2007. Besides the natural occurrence of endophytes, many studies are being carried out with genetically modifi ed microorganisms (GMM) to evaluate host colonization (Germaine et al 2004, Ferreira et al 2008.…”
Section: Abstract: Insecta Oryza Sativa Endophytic Microorganismmentioning
confidence: 99%
“…Studies have shown that fungal endophytes are neither incident residents nor merely latent pathogens of plant hosts but also exert several beneficial effect. Their functional roles may be attributed to protect the host from the insect pests (Azevedo et al 2000), fungal pathogens (Arnold et al 2003;Dingle and McGee 2003), or increase the host fitness in harsh environments (Redman et al 2002). Besides, endophytic fungi have been recognized as repository of biologically active substances (Tan and Zou 2001).…”
Section: Introductionmentioning
confidence: 99%